Syntactic thinking by Ibn Malek in his explanation for Alkafia Ashafiah principles and syntactic rules (Sebha University Conference Proceedings, 2024)
This research is about Ibn malek's syntactic thinking in his famous books (Sharh Alkafia Ashafia) to present the rules and principles which give his arguments a very strong linkage and strength so these arguments were so logical and rational this study is divided as following: Introduction consists of: importance of study , purpose of study, problem of study, reasons why this topic was chosen previous studies , research plan and research terms then after that first topic which contains on Ibn maleks curriculum vitae  poem Al Kafiya Shafiyah explanation to this poem then second topics talks written principles by ibn malik such holy Quran prophet teachings arabic talk third mental evidence analogy consensus continuity finally fourth total two mentioned all definitions examples end conclusion results six points five recommendations